Soil Health and Its Improvement Through Novel Agronomic and Innovative Approaches - Shahane, Amit Anil; Shivay, Yashbir Singh (Frontiers in Agronomy, 2021)
Soil is important natural resource providing water, nutrient and mechanical support for plant growth. In agroecosystem, continuous manipulation of soil is going on through addition of input, removal of nutrients, changing water balance and microbial life. These changes affect the soil properties (physical chemical and biological) and deviation of these properties from the normal status is controlled by soil buffering capacity and soil resilience. If these changes are beyond the reach of soil resilience then soil loses its original state leading to soil degradation. To maintain soil in healthy condition it is needed to maintain the soil physical, chemical and biological properties and this is possible through adoption of different agronomic approaches. The diversification of nutrient sources with emphasis on the organic sources, adopting principles of conservation agriculture, enhancing soil microbial diversity, efficient resource recycling through integrated farming system and amendment addition for correcting the soil reactions are the potential options for improving soil health and discussed in this review. Further, article reviewed the concept of soil health and its development, issues related with soil health and indicators of healthy soil. At the same time, the impact of ill health of soil on the crop productivity and resource use efficiency reported in different part of the world in recent years is also reviewed. The agro-techniques such as green and brown manuring in arable land and agroforestry on degraded and marginal land were followed on piece meal basis and that to for economic gain. The potential of these and several other options for maintaining soil health is recognized evaluated and quantified for their wider application. Use of crop residue, agro-industrial waste and untreated mineral or industrial waste (basic slag, phosphogypsum, etc.) as soil amendments has hues potential to maintain healthy soil along with serving as source of crop nutrition. In our review emphasis has been given to evaluate and quantified the presently followed agro-techniques for their contribution to soil health improvement across agro-climatic regions for their wider implications. Further, emphasis has been given for innovative approaches for soil health management rather than mere application of manures and fertilizers for crop nutrition.